Chronic Infection and Nodule Formation following Deoxycholate Injection - Shahid, Shahab; Al-Hassani, Fawaz (Archives of Plastic Surgery, 2022)
Aqualyx (Marllor International Ltd, Rimini, Italy) was originally developed in Italy by Professor Pasquale Motolese and has been commercially available since 2009. It is a deoxycholate, aqueous gelatinous solution mixed with saline and buffering compounds. It is the only drug approved by the European Union for the reduction in localized fat. Aqualyx is sold exclusively to doctors and nurses trained in intralipotherapy. In the case of our patient, the product administered was advertised as Aqualyx, but was not administered by a trained health professional and was administered too superficially. The patient developed severe pain following the injection and was unable to sit for several weeks. There was localized skin necrosis, and palpable collections where the injection was administered. Our initial suspicion was development of an abscess or hematoma. To characterize further, we arranged an ultrasound scan that showed a “superficial hypoechoic lesion” but no deeper infection or spread. The numerous painful nodules ruptured onto the skin surface, resulting in purulent and bleeding lesions. This case demonstrates the importance of appropriate training and competence in performing cosmetic procedures including injections and fat dissolving treatments.
Keywords: aqualyx; cosmetics; complication; training; safety